2016
DOI: 10.1515/raon-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Tenckhoff tunneled peritoneal catheter placement in the palliative treatment of malignant ascites: technical results and overall clinical outcome

Abstract: BackgroundTo assess the technical and clinical outcome of percutaneous insertion of tunneled peritoneal catheters in the palliative treatment of refractory malignant ascites and to determine the safety and feasibility of intraperitoneal administration of cytotoxic drugs through the tunneled catheter.Materials and methodsConsecutive patients palliatively treated with a tunneled peritoneal catheter to drain the malignant ascites were identified. Patients’ medical history, procedural and clinical follow-up data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…The underlying malignancy, its symptoms, and prognosis are important to direct clinical decision making in MA drainage. The life expectancy of patients with refractory MA is very poor, with an overall survival ranging from 1 to 6 months in nonovarian cancer and 10–24 months in ovarian cancer 8,12,44. Patients with refractory MA with a longer life expectancy, such as patients with gynecologic tumors, may also benefit from the use of a tunneled catheter for a longer period, compared with patients with more aggressive tumors such as gastrointestinal malignancies 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying malignancy, its symptoms, and prognosis are important to direct clinical decision making in MA drainage. The life expectancy of patients with refractory MA is very poor, with an overall survival ranging from 1 to 6 months in nonovarian cancer and 10–24 months in ovarian cancer 8,12,44. Patients with refractory MA with a longer life expectancy, such as patients with gynecologic tumors, may also benefit from the use of a tunneled catheter for a longer period, compared with patients with more aggressive tumors such as gastrointestinal malignancies 8…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chemotherapy should not be a contraindication to catheter placement 27,47. An additional advantage of TPC or PPP for ascites drainage is that intraperitoneal infusion of chemotherapy (cisplatin) or active targeted therapeutic agents (catumaxomab) is possible 8,31…”
Section: Discussionmentioning
confidence: 99%
“…Tunnelled indwelling catheters are catheters which are inserted into the abdomen, with residual tubing left outside of the abdomen to enable access . The National Institute for Health and Clinical Excellence in the United Kingdom recommends that this type of drainage system be considered in patients with treatment‐resistant recurrent malignant ascites .…”
Section: Discussionmentioning
confidence: 99%
“…5,16,17 Tunnelled indwelling catheters are catheters which are inserted into the abdomen, with residual tubing left outside of the abdomen to enable access. [18][19][20] The National Institute for Health and Clinical Excellence in the United Kingdom recommends that this type of drainage system be considered in patients with treatmentresistant recurrent malignant ascites. 21 Several studies have demonstrated the cost-effectiveness of tunnelled indwelling catheters over large volume paracentesis, particularly if the patient requires frequent paracentesis.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…Current treatments for advanced stages of ovarian cancer include either primary cytoreductive surgery followed by adjuvant chemotherapy or neoadjuvant chemotherapy followed by interval cytoreductive surgery and adjuvant chemotherapy 4, 5. The use of neoadjuvant treatments remains controversial, 1 although the American Society of Clinical Oncology recently recommended their use 3 . The use of antiangiogenic agents such as bevacizumab, a humanized anti-vascular endothelial growth factor (VEGF) monoclonal antibody, is another possibility for treating ovarian cancer 6 .…”
Section: Introductionmentioning
confidence: 99%